The complete web development course : build 15 projects - Issam (Packt Publishing, 2018)
"The course will take you from learning the basics to mastering the most advanced web development techniques. Taking this course will help you be ready to build powerful and responsive websites to a highly professional degree using today's most advanced and up to date web technologies within a few weeks from now. This course is divided into 10 perfectly structured chapters consisting of 77 hours of crystal clear and 100% hands on engaging lectures. You will first learn the basic concepts, and straight after that apply them in easy practical examples. Then you will easily navigate to more advanced concepts and use them to build more complex applications. Once you have finished the chapter, you will then move to a bigger challenge where you will confidently build a real life full professional project using the skills you acquired in that chapter combined with previous ones."--Resource description page